Medical assistance in dying in Canada: a multidisciplinary Pan-Canadian Delphi study to inform clinical practice guidance documents and plan a research agenda - Melissa Henry; Justine Albert; Sabrina Chan Chun Kong; James Downar; Madeline Li; Sally Thorne; Brian Mishara; Justin Sanders; Isabelle Marcoux; Diane Tapp; Romayne Gallagher; Manon Guay; et al. (BMC Palliative Care, 2026)
Abstract Objective Medical assistance in dying (MAiD) requires careful attention to suffering, yet clinical practice guidance documents provide variable detail on how multidimensional suffering can be explored and addressed. This Delphi study sought expert consensus on potential improvements to clinical practice guidance documents and research priorities related to suffering in MAiD. Methods A multidisciplinary panel of 54 experts participated in a modified e-Delphi study. Candidate items were developed from a previously published scoping review conducted by members of the research team and discussions from a National Knowledge Dissemination and Research Planning Meeting conducted as part of a broader knowledge-translation initiative. The resulting items were then prioritized through three Delphi survey rounds. Results Consensus recommendations emphasized the need to move beyond MAiD assessment as a discrete eligibility determination and toward a more longitudinal, interdisciplinary approach to understanding and responding to suffering. The strongest priorities included earlier integration of psychosocial and palliative approaches throughout the illness trajectory, rather than only once MAiD is being considered; continued support for patients throughout the MAiD process, including those deemed ineligible; and greater attention to mental health stigma, social determinants of health, culturally responsive care, and the bio-psycho-social-existential dimensions of suffering. Conclusion Findings provide a framework for strengthening MAiD guidance documents by supporting consistent, interdisciplinary approaches to exploring and addressing suffering. Embedding palliative and psychosocial care earlier in the illness trajectory may help ensure that potentially modifiable sources of suffering are identified and addressed while respecting patient autonomy and supporting high-quality, patient-centered MAiD care.